Bone morphogenetic protein‐4 modulates proliferation and terminal differentiation of fetal hepatic stem/progenitor cells. Issue 9 (31st October 2016) - Goto, Fumio; Kakinuma, Sei; Miyoshi, Masato; Tsunoda, Tomoyuki; Kaneko, Shun; Sato, Ayako; Asano, Yu; Otani, Satoshi; Azuma, Seishin; Nagata, Hiroko; Kawai‐Kitahata, Fukiko; Murakawa, Miyako; et al.
Aim: Fetal hepatic stem/progenitor cells, called hepatoblasts, play central roles in liver organogenesis; however, molecular mechanisms regulating proliferation and terminal differentiation of such cells have not been completely elucidated. Bone morphogenetic protein‐4 (BMP‐4) is essential for the development of stem cells in various tissues, but its function in regulating the phenotype of hepatoblasts after the mid‐gestational fetal stage remains unclear. The aim of this study is to clarify a functional role for BMP‐4 in proliferation and terminal differentiation of murine hepatoblasts in mid‐gestational fetal livers. Methods: A functional role for BMP‐4 in proliferation and terminal differentiation of murine hepatoblasts was validated by assay of colony formation, biliary luminal formation, and hepatic maturation using primary hepatoblasts in vitro . Molecular mechanisms regulating such effects of BMP‐4 on primary hepatoblasts were also analyzed. Results: Stimulation of BMP‐4 upregulated phosphorylation of Smad1/5 in hepatoblasts. Bone morphogenetic protein‐4 significantly suppressed colony formation of primary hepatoblasts in a dose‐dependent manner, significantly suppressed cholangiocytic luminal formation of hepatoblasts, and promoted hepatic maturation of primary hepatoblasts. Stimulation of BMP‐4 regulated the activation of several mitogen‐activated protein kinases, such as extracellular signal‐regulated kinase, Akt, p38 mitogen‐activated protein kinase, and calcium/calmodulin‐dependent protein kinase IIα in primary hepatoblasts. Moreover, Wnt5a, a molecule regulating cholangiocytic luminal formation, and BMP‐4 coordinately suppressed proliferation and cholangiocytic luminal formation of hepatoblasts. Conclusion: This study shows that BMP‐4‐mediated signaling controls proliferation and terminal differentiation of fetal hepatic stem/progenitor cells.